1994
DOI: 10.1093/oxfordjournals.annonc.a058736
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel (TAXOL®) concentrations in brain tumor tissue

Abstract: These findings suggest that paclitaxel may have a place in brain tumor therapy. The low concentration in normal brain tissue, as observed in one patient, may suggest, however, that the drug does not cross the intact bloodbrain barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 3 publications
1
60
0
Order By: Relevance
“…8 Our results suggest that repeated administration of oxycodone not only causes upregulation of P-gp, but also significantly affects the transport of paclitaxel across the BBB, liver, and kidney. These findings have potentially important implications on the therapeutic activity of paclitaxel especially in the treatment of brain, hepatic and renal tumors [19][20][21]39,40 when coadministered with oxycodone. It should be noted that oxycodone levels would have been quantified in the oxycodone tolerant animals if radiolabelled oxycodone was available.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 Our results suggest that repeated administration of oxycodone not only causes upregulation of P-gp, but also significantly affects the transport of paclitaxel across the BBB, liver, and kidney. These findings have potentially important implications on the therapeutic activity of paclitaxel especially in the treatment of brain, hepatic and renal tumors [19][20][21]39,40 when coadministered with oxycodone. It should be noted that oxycodone levels would have been quantified in the oxycodone tolerant animals if radiolabelled oxycodone was available.…”
Section: Discussionmentioning
confidence: 98%
“…For the management of cancer, oxycodone is usually coadministered with many chemotherapeutic agents, the majority of these agents are P-gp substrates. [19][20][21][22] Changes in P-gp expression upon repeated administration of oxycodone may affect the uptake, the distribution, and the potency of these chemotherapeutic agents which in turn may lead to ineffective cancer therapy. The goal of this study was to investigate the influence of multiple administration of oxycodone on the level of expression of P-gp in different tissues in Sprague Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the drug penetrates the blood-brain barrier poorly (Glantz et al, 1995). Despite this, there is at present some evidence that paclitaxel (Heimans et al, 1994). In line with this, several reports have indicated that the drug can be effective against experimental brain tumours, when it is delivered either from biodegradable polymer implants (Walter et al, 1996) or from liposome-encapsulated vehicles (Riondel et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although paclitaxel has shown potent in vitro activity in human glioma lines (12 -14), low concentrations of paclitaxel in human PBT samples and undetectable levels in normal brain tissue have been shown (15). Thus, the failure to achieve adequate paclitaxel deposition in a glioma with a partially intact BBB may account in part for paclitaxel's poor efficacy for PBT (16,17).…”
mentioning
confidence: 99%